Cardiovascular disease and risk of lung cancer incidence and mortality: A nationwide matched cohort study - Wang, Ce; Lu, Donghao; Cronin-Fenton, Deirdre; Huang, Chen; Liew, Zeyan; Wei, Dang; Qin, Guoyou; Yu, Yongfu; Li, Jiong (Frontiers in Oncology, 2022)
Purpose: Previous studies have suggested a link between cardiovascular disease (CVD) and subsequent lung cancer development. However, empirical evidence on the association of CVD, particularly for type-specific CVDs, with lung cancer incidence and survival, remains limited. Methods: The cohort study included 306,285 patients with CVD and 1,222,140 individuals without CVD. We performed stratified Cox regression to estimate hazard ratio (HR). Results: During up to 42 years of follow-up, 243(0.08%) and 537(0.04%) participants were diagnosed with lung cancer among CVD patients and matched individuals, respectively. Patients with CVD had a 67% increased risk of lung cancer (HR: 1.67, 95% confidence interval [CI]:1.42- 1.96). The increased risks were observed in patients with heart disease (1.93,1.30-2.85), vascular disease (1.88,1.35-2.61), and hypertensive disease (1.46,1.15-1.85), respectively. Patients with CVD had a 95% increased risk of lung cancer mortality (1.95,1.50-2.55), especially vascular disease (3.24, 1.74-6.02) and heart disease (2.29,1.23-4.26). Patients with CVD diagnosed in middle adulthood (>40 years old) tended to have higher incidence risk (3.44, 2.28-5.19) and mortality (3.67, 1.80-7.46) than those diagnosed at younger ages. Conclusions: Our findings on the association of CVD diagnosis, especially heart and vascular disease, with increased risk of lung cancer incidence and mortality, suggest that CVD may contribute to the development and worse survival of lung cancer. In particular, people with CVD diagnosed in middle adulthood (>40 years old) would benefit from early preventive evaluation and screening for lung cancer.